2014
DOI: 10.1186/1471-2393-14-337
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration, vital exhaustion, and odds of spontaneous preterm birth: a case–control study

Abstract: BackgroundPreterm birth is a leading cause of perinatal morbidity and mortality worldwide, resulting in a pressing need to identify risk factors leading to effective interventions. Limited evidence suggests potential relationships between maternal sleep or vital exhaustion and preterm birth, yet the literature is generally inconclusive.MethodsWe examined the relationship between maternal sleep duration and vital exhaustion in the first six months of pregnancy and spontaneous (non-medically indicated) preterm b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 35 publications
2
42
1
2
Order By: Relevance
“…There is a large literature demonstrating that maternal sleep disturbance, such as sleep-disordered breathing, short sleep duration, and poor sleep quality are common during pregnancy and have strong associations with poor outcomes such as gestational hypertension and preeclampsia, [15][16][17][18] gestational diabetes, 16,19,20 fetal growth restriction, [21][22][23] and preterm birth. 17,21,24,25 Importantly, the latter outcomes are known risk factors for stillbirth. 26 Since nocturnal events may influence pregnancy outcomes, possibly by induction of inflammatory and oxidative stress responses, endothelial damage, and metabolic derangement, [27][28][29] the link between maternal sleep and stillbirth warrants urgent investigation.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large literature demonstrating that maternal sleep disturbance, such as sleep-disordered breathing, short sleep duration, and poor sleep quality are common during pregnancy and have strong associations with poor outcomes such as gestational hypertension and preeclampsia, [15][16][17][18] gestational diabetes, 16,19,20 fetal growth restriction, [21][22][23] and preterm birth. 17,21,24,25 Importantly, the latter outcomes are known risk factors for stillbirth. 26 Since nocturnal events may influence pregnancy outcomes, possibly by induction of inflammatory and oxidative stress responses, endothelial damage, and metabolic derangement, [27][28][29] the link between maternal sleep and stillbirth warrants urgent investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Our sample size was relatively large compared with the limited actigraphic sleep studies in pregnant women . Unlike most pregnancy outcome research primarily focusing on nighttime sleep , objective and self‐reported measures of nighttime and daytime sleep were assessed concurrently in the present study. There are also several limitations to our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…More than 75 percent of pregnant women complain of disturbed sleep during the third trimester , approximately 15–36 percent report significant depressive symptomatology , and up to 19.2–47 percent experience daytime sleepiness . These symptoms are distressing to pregnant women and are linked with adverse obstetric conditions, including gestational hypertension and diabetes , prolonged labor and cesarean delivery , preterm labor , small‐for‐gestational‐age infants , and postpartum depression . Available data on the association between sleep disturbances and symptoms of depression and daytime sleepiness in pregnant women are sparse and methodological limitations have been acknowledged, with most studies relying on participants' subjective and retrospective reports of sleep .…”
mentioning
confidence: 99%
“…1 Available evidence suggests that sleep disturbances during pregnancy are associated with adverse perinatal outcomes, including maternal depression, preeclampsia, and preterm birth. 24 For example, investigators have reported that short sleep duration (6 or fewer nightly hours) in early pregnancy is associated with elevated trimester-specific blood pressures, 3 increased risks of preeclampsia 3 and spontaneous preterm birth. 4 Given the adverse maternal and perinatal health outcomes associated with disturbed sleep during pregnancy, it is important to identify factors associated with disturbed sleep that may serve as clinically useful screening indicators for poor sleep health.…”
Section: Introductionmentioning
confidence: 99%